2014
DOI: 10.1590/s1982-56762014000600005
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of Tomato chlorosis virus alone and in mixed infection with begomoviruses in two tomato fields in the Federal District and Goiás state, Brazil

Abstract: Tomato chlorosis virus (ToCV), a species in the Crinivirus genus, was first reported in tomatoes in Brazil (state of São Paulo) in 2008. This was followed by reports in several other Brazilian states. Tomato plants with chlorotic spots and leaf roll symptoms are frequently observed in tomato fields with high whitefly populations in Central Brazil. These plants could be infected with a begomovirus, a crinivirus, or with both viruses. A survey of two selected tomato fields in the Federal District and Goiás State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
13
0
7
Order By: Relevance
“…Outbreaks of golden mosaic disease in fresh-market tomatoes are currently common in Brazil, even with the use of cultivars resistant to begomoviruses (Macedo et al, 2014). These cultivars usually carry the Ty-1 gene, which is the most widely used gene that confers resistance to tomato yellow leaf curl virus and other begomoviruses (Zamir et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outbreaks of golden mosaic disease in fresh-market tomatoes are currently common in Brazil, even with the use of cultivars resistant to begomoviruses (Macedo et al, 2014). These cultivars usually carry the Ty-1 gene, which is the most widely used gene that confers resistance to tomato yellow leaf curl virus and other begomoviruses (Zamir et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This disease is caused by the crinivirus tomato chlorosis virus (ToCV), which is also transmitted by whiteflies. This disease has rapidly spread across the main tomato production areas in Brazil (Barbosa et al, 2011;Macedo et al, 2014). ToCV is the only crinivirus that has been reported in tomatoes in Brazil (Barbosa et al, 2008(Barbosa et al, , 2011, and little genetic variability has been found among isolates (Albuquerque et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of ToCV in tomato, mixed infections with other viruses have been described to be frequent in several countries. The viruses involved in mixed infections with ToCV include tomato yellow leaf curl virus (a monopartite Old World begomovirus transmitted by B. tabaci ) (Martínez‐Zubiaur et al , ), tomato severe rugose virus (a bipartite New World begomovirus transmitted by B. tabaci ) (Macedo et al , ), pepino mosaic virus (a potexvirus transmitted by mechanical contact) (Davino et al , ) and tomato torrado virus (a torradovirus transmitted by B. tabaci and T. vaporariorum ) (Gómez et al , ). The above papers describing mixed infections with begomoviruses reported that the symptoms observed in plants infected with both are more severe than those induced by the begomovirus alone.…”
Section: Epidemiologymentioning
confidence: 99%
“…Tomatoes can be naturally infected by one or both viruses, as reported by Macedo et al . () after analysing their incidence in leaf samples from 150 tomato plants collected in central Brazil. Forty‐eight percent of the plants were doubly infected, while 32% and 20% were infected only with ToCV or ToSRV, respectively.…”
Section: Introductionmentioning
confidence: 99%